Agency theory: the times, they are a-changin'. Issue 1 (8th February 2016) - Bendickson, Josh; Muldoon, Jeff; Liguori, Eric; Davis, Phillip E
Abstract : Purpose: – Theories develop over time and are influenced by both events and people. Looking primarily at the applications between contracting principal-agent relationships, the purpose of this paper is to explore how agency theory emerged from a number of economic and social developments. In doing so, the authors explain how this once dominant theory comes up short regarding varying realms of entrepreneurship as well as with multiple modern business phenomena. Design/methodology/approach: – The authors first present a brief overview of agency theory. Second, the authors identify major events and people and address how they impacted the development of agency theory. Third, the authors provide insights on agency theory across three contexts (strategic entrepreneurship, social entrepreneurship, and family business). Implications, limitations, and future research directions are then offered. Findings: – The authors provide a deeper understanding of agency theory, thus broadening its underpinnings and enabling readers to more readily understand why agency theory is limited in its explanation of certain and modern business phenomena. The authors find that some of the seminal influences to agency theory are quite dated which has limited its explanatory power in terms of the modern day business and with more recent disciplines such as entrepreneurship. Research limitations/implications: – The authors are limited by their choices of major events that influenced agency theory at the expense of not being able to include everything that may have impacted the theory over time. These limitations, however, are offset by the research implications. As the authors highlight the underpinning of agency theory, the authors subsequently provide scholars and practitioners with five primary boundary conditions, each of which are in need of attention for agency theory to maintain relevant explanatory power. Originality/value: – A deeper understanding of agency theory can be gained by looking at its underpinnings. By presenting numerous principal-agent conflicts and demonstrating areas in which it has fallen short (i.e. entrepreneurship and more recent business phenomenon), we shed light on the obstacles agency theory must overcome in order to maintain its position as a prominent theory.